SISTEM INFORMASI PENILAIAN KINERJA KARYAWAN PADA PT.SETIAJAYA MOBILINDO MENGGUNAKAN METODE RATING SCALE BERBASIS WEB - Richard Suryanto, - (2018)
In the current era of information technology, the gap in the world of work is a very broad benchmark, coupled with technology that is so growing rapidly. PT. Setiajaya Mobilindo is one of the authorized dealers of Toyota who function in terms of vehicle sales, service and sell spare parts where these three functions are intended specifically for various types of vehicles branded Toyota. The problems that often arise is where in conducting the assessment of the employees are still traditional plus the assessment is done using data pickup. The results obtained cause the Assessments presented are inaccurate and inefficient. Regardless of this, the company will get small problems if the assessment is not done computerized and not transparent because an employee will feel comfortable in the zone so that it makes the employee will not improve the quality of its performance and it will be able to slow the progress of the company . To prevent the occurrence of this writer using rating scale method to make a web based employee performance appraisal system where the language used is PHP programming language, and connecting application that connect PHP and MySQL with xampp application and Sublime Text 3 as tools for coding. Implementation of the program can overcome the problems of running systems such as, more leverage in data processing and report generation.